Student reviewers of teaching practice: Reflections on the design & experience of participants - Marie, Jenny; Hansen, Jesper; Hazen, Melissa; Irarrazabel Elliott, Manuela; Piccoli, Giacomo; Thorogood, Joe (International Journal for Students as Partners, 2018)
This case study focuses on the benefits and challenges of students and staff working in partnership to review virtual learning environments as part of a wider review of an academic course. The paper considers how it enables a more rounded view of the course to be gained and how students identified possible enhancements to online sites in their own departments from the experience. Most issues raised by students related to the organization of the sites, with differences between students and staff in both the approach they thought should be taken to this and the importance placed upon it. These different perspectives make dialogue and respect very important in this area of student-staff partnership.